Structurally and semantically coherent deep image inpainting - Sami, Mirza Tanzim; Khan, Ehsanul Amin; Rhidita, Ishrat Naiyer (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.